Assessing the security of crude oil supply chain: The case of China - Jingye Liu; Fengqi Guo; Ying Shi; Rijia Ding; Zhen Chen (Energy Strategy Reviews)
The recurrence of international geopolitical events has intensified tensions in global energy supply chains. As a major crude oil consumer, China urgently needs to identify vulnerabilities within its crude oil supply chain (COSC) and implement targeted measures to safeguard national energy security. In this study, a risk evaluation index system was constructed based on the entire life cycle in COSC. Then, the phased and overall prominent risks in the China's COSC from 2012 to 2022 were identified through a two-phase DEA-like model. Furthermore, the evolution of the comprehensive security level of COSC was assessed throughout the study period. Specifically, the phased risks of China's COSC mainly focused on strategic petroleum reserves (SPR) in the midstream application stage and refined oil trade in the downstream consumption stage. Additionally, China's COSC primarily confronted overall risks involving domestic crude oil supply potential, geopolitical imports, maritime transportation, and domestic oil consumption. Although the security level of China's COSC showed an upward trend from 2012 to 2022, the security of the upstream still lagged behind that of the midstream and downstream. Hence, policy recommendations to enhance China's COSC security include advancing the exploration and development of unconventional oil, strengthening international energy cooperation and the autonomy of maritime transportation, expanding the SPR, increasing the proportion of renewable energy, and establishing a risk early warning platform.